Moving "Up and Out" Together: Exploring the Mother–Child Bond in Low‐Income, Single‐Mother‐Headed Families. Issue 3 (26th October 2016) - Freeman, Amanda L.
Abstract: Bearing children is often viewed as negatively impacting the social mobility of low‐income single mothers. This analysis draws on 66 in‐depth interviews with low‐income, single‐mother participants in an antipoverty program in Boston. The author argues that the mother–child relationship is at the center of efforts by these single mothers to move out of poverty. Interviewees repeatedly expressed the primacy of their children's needs being met in order for them to move forward. Mothers tried to include their children in efforts to move out of poverty, thus fulfilling the role of a "good mother" while exhibiting proper behavior for a poor person trying to achieve economic independence. The data here highlight the limitations of policy initiatives that fail to acknowledge the centrality of children's well‐being to the lives of single mothers and suggest that the mother–child bond may be an untapped resource for policies and programs serving this community.